2002
DOI: 10.1111/j.1749-6632.2002.tb04466.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Motors Involved in Chromaffin Cell Secretion

Abstract: Neurosecretory cells, including chromaffin cells, possess a mesh of filamentous actin underneath the plasma membrane. It has been proposed that filamentous actin network separates the secretory vesicles into two compartments: the reserve pool and the release-ready vesicle pool. Disassembly of chromaffin cell cortical filamentous actin in response to stimulation allows the movement of vesicles from the reserve pool into the release-ready vesicle pool. Electron microscopy of cytoskeletons revealed the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…In these systems, actin serves a scaffolding role and is required to anchor secretory vesicles as a readily releasable pool (Sankaranarayanan et al, 2003). In some cases, this anchoring requires a myosin (Rose et al, 2002;Rudolf et al, 2002), whereas in other cases, such as GLUT4 delivery to the adipocyte plasma membrane, a plus-enddirected unconventional myosin, myo1C, may play a role in vesicle delivery across the barrier toward the plasma membrane (Bose et al, 2002). In peripheral regions there is a higher percentage of plus ends facing outward so a plusend-directed myosin would be appropriate for vesicle trafficking outward for exocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…In these systems, actin serves a scaffolding role and is required to anchor secretory vesicles as a readily releasable pool (Sankaranarayanan et al, 2003). In some cases, this anchoring requires a myosin (Rose et al, 2002;Rudolf et al, 2002), whereas in other cases, such as GLUT4 delivery to the adipocyte plasma membrane, a plus-enddirected unconventional myosin, myo1C, may play a role in vesicle delivery across the barrier toward the plasma membrane (Bose et al, 2002). In peripheral regions there is a higher percentage of plus ends facing outward so a plusend-directed myosin would be appropriate for vesicle trafficking outward for exocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, chemical stimulation causes the regulatory subunit of MLCK to become phosphorylated in a calcium-dependent manner proportional to the magnitude of the stimulus (Nicotera et al, 1986;Gutierrez et al, 1989). Furthermore, granule recruitment to the readily releasable pool has been shown to require phosphorylation of MLCK and activation of myosin (Kumakura et al, 1994;Rosé et al, 2002). Recent work found that expression of a phosphorylation-incompetent form of myosin II regulatory light chain decreased the kinetics of catecholamine release from single granules.…”
Section: Discussionmentioning
confidence: 99%
“…However, Myo2 is also associated with the Golgi complex, vesicles emanating from the TGN and secretory granules, suggesting that it participates in constitutive and stimulated secretion [60,64,86].…”
Section: Myosin II (Myo2) In Constitutive and Stimulated Secretionmentioning
confidence: 98%